Electric vehicles performing last-mile delivery in B2C e-commerce: An economic and environmental assessment. Issue 1 (3rd January 2022) - Siragusa, Chiara; Tumino, Angela; Mangiaracina, Riccardo; Perego, Alessandro
Abstract: The proliferation of e-commerce in the recent years has been recognized to have a huge impact on transportation owing to the increasing need for last-mile deliveries in urban areas. Further, it is claimed to be responsible for the rising number of vans moving in cities, considerably impacting environmental sustainability. In this context, electric vehicles (EVs) could substitute internal combustion engine vehicles (ICEVs) to mitigate their harmful impact on the environment. This work aims to provide a comparison between the EVs and the ICEVs used to perform last-mile deliveries in business-to-consumers (B2C) e-commerce, considering both economic and environmental perspectives. The life cycle assessment method is adopted for the evaluation of environmental impact. However, economic assessment is based on the total cost of ownership analysis, which allows the comparison between the two types of vehicles throughout the ownership period. The analysis was conducted considering an Italian city (Milan). The use of EVs proved to be economically beneficial when an 8-year timeframe was considered. Even if the initial investment for EVs is high, owing to a purchasing price that is nearly double when compared to ICEVs, the lower operating expenditure makes EVs a competitive option. Considering the environmental perspective, EVs turned out to be the best option in all the scenarios assumed. In particular, EVs lead to a decrease in greenhouse gas (GHG) emissions by 17% (in the 20 km/day case) to by 54% (in the 120 km/day case), or even more if a higher daily mileage is considered.